1993
DOI: 10.1073/pnas.90.23.11346
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing the human GLUT4/muscle-fat facilitative glucose transporter protein exhibit efficient glycemic control.

Abstract: To examine the physiological role of the GLUT4/muscle-fat specific facilitative glucose transporter in regulating glucose homeostasis, we have generated transgenic mice expressing high levels of this protein in an appropriate tissue-specific manner. Examination of two independent founder lines demonstrated that high-level expression of GLUT4 protein resulted in a marked reduction of fasting glucose levels (=70 mg/dl) compared to wild-type mice ("'130 mg/dl). Surprisingly, 30 min following an oral glucose ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
1
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 46 publications
9
78
1
3
Order By: Relevance
“…These observations are in agreement with previous studies that reported enhanced glucose tolerance and insulin sensitivity in mice with a 1.3-fold increase of glycogen content in skeletal muscle due to enhanced glycogen synthesis (Patel et al 2008). Similarly, skeletal muscle from transgenic mice overexpressing Glut4 shows an increase in glycogen content accompanied by enhanced glucose tolerance and insulin sensitivity (Liu et al 1993). Although changes in expression of Glut4 and glycogen storage have been associated with enhanced glucose tolerance and insulin sensitivity, our study reveals for the first time the involvement of MED13 in skeletal muscle glucose metabolism and its impact on hepatic steatosis in the HFD-induced insulin-resistant state.…”
Section: Modulation Of Hepatic Metabolism By Skeletal Muscle Med13supporting
confidence: 93%
“…These observations are in agreement with previous studies that reported enhanced glucose tolerance and insulin sensitivity in mice with a 1.3-fold increase of glycogen content in skeletal muscle due to enhanced glycogen synthesis (Patel et al 2008). Similarly, skeletal muscle from transgenic mice overexpressing Glut4 shows an increase in glycogen content accompanied by enhanced glucose tolerance and insulin sensitivity (Liu et al 1993). Although changes in expression of Glut4 and glycogen storage have been associated with enhanced glucose tolerance and insulin sensitivity, our study reveals for the first time the involvement of MED13 in skeletal muscle glucose metabolism and its impact on hepatic steatosis in the HFD-induced insulin-resistant state.…”
Section: Modulation Of Hepatic Metabolism By Skeletal Muscle Med13supporting
confidence: 93%
“…Similar to the muscle-specific GLUT1 overexpression model, transgenic mice overexpressing GLUT4 in both muscle and adipose tissue also show a marked reduction in fed and fasted glucose levels in addition to improved glucose tolerance (12). Similar to the muscle-specific GLUT1 overexpressors, muscle/fat-specific GLUT4 overexpressors also demonstrate increases in circulating lactate and b-hydroxybutyrate levels.…”
Section: Figurementioning
confidence: 78%
“…Similar to the muscle-specific GLUT1 overexpressors, muscle/fat-specific GLUT4 overexpressors also demonstrate increases in circulating lactate and b-hydroxybutyrate levels. In contrast to the musclespecific GLUT1 overexpressors, insulin levels are appropriately decreased in response to the basal hypoglycemia present in the muscle/fat-specific GLUT4 overexpressors (12). In addition, the muscle/fat-specific GLUT4 overexpressors demonstrate increased glucose disposal in response to insulin during a clamp, in contrast to the insulin resistance in muscle-specific GLUT1 overexpressors (11).…”
Section: Figurementioning
confidence: 98%
“…Basal muscle glycogen levels in both models were normal but insulin-stimulated glycogen synthesis was reduced (22,(25)(26)(27). In contrast, transgenic mice overexpressing GLUT4 (28,29) and GLUT1 (28,30,31) in muscle had increased glucose uptake, increased muscle glycogen content, and improved glucose tolerance. This improvement in glucose tolerance occurred despite skeletal muscle insulin resistance as determined by euglycemichyperinsulinemic clamp (28) and in ex-vivo muscle studies (31,32).…”
Section: Discussionmentioning
confidence: 95%